TINJAUAN LITERATUR: IMPLEMENTASI MANAJEMEN BANDWIDTH HIERARCHICAL TOKEN BUCKET (HTB) DAN PER CONNECTION QUEUE (PCQ) - Muhamad Mukhlisin (LPPM Universitas Dhyana Pura, 2025)
In the digital era, the need for an internet connection has become a necessity for everyday life. All aspects of life are already influenced by internet connections. Therefore, fair and efficient bandwidth distribution is a necessity. This is the background for researchers to conduct a literature study related to the comparison between two bandwidth management methods, namely Hierarchical Token Bucket (HTB) and Per Connection Queue (PCQ). The selection of the two bandwidth distribution methods refers to their frequent use for bandwidth management by considering the number or level of users to provide equal access for all internet users. This study will analyze the comparison of the quality of the HTB and PCQ bandwidth management methods based on four parameters, namely throughput, jitter, packet loss and delay. With this method, it is expected to determine the most efficient bandwidth distribution. The research method used in this study is the Systematic Literature Review. Systematic Literature Review is a systematic and comprehensive method for identifying, evaluating and synthesizing research results to obtain results that reflect the entire research. One of the standard methods used in the Systematic Literature Review is PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses). The results of the study indicate that the HTB bandwidth management method has advantages over the PCQ method in the parameters of throughput, jitter and delay. While in the packet loss parameter, the HTB method has the same ability as the PCQ method.